2015
DOI: 10.3389/fpls.2015.00746
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Arabidopsis FCS-Like Zinc finger genes is differentially regulated by sugars, cellular energy level, and abiotic stress

Abstract: Cellular energy status is an important regulator of plant growth, development, and stress mitigation. Environmental stresses ultimately lead to energy deficit in the cell which activates the SNF1-RELATED KINASE 1 (SnRK1) signaling cascade which eventually triggering a massive reprogramming of transcription to enable the plant to survive under low-energy conditions. The role of Arabidopsis thaliana FCS-Like Zinc finger (FLZ) gene family in energy and stress signaling is recently come to highlight after their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 49 publications
(89 reference statements)
0
45
0
1
Order By: Relevance
“…SnRK1 is a central regulator of growth during energy deficit. Previously we demonstrated that energy status and SnRK1 regulate the expression of FLZ genes (Jamsheer K and Laxmi, ). Here we show that two FLZ proteins, FLZ6 and FLZ10, negatively regulate the level of SnRK1α1.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…SnRK1 is a central regulator of growth during energy deficit. Previously we demonstrated that energy status and SnRK1 regulate the expression of FLZ genes (Jamsheer K and Laxmi, ). Here we show that two FLZ proteins, FLZ6 and FLZ10, negatively regulate the level of SnRK1α1.…”
Section: Discussionmentioning
confidence: 95%
“…FLZ10 was also found to be induced in response to mild starvation; however, prolonged starvation repressed its transcription. Further, FLZ6 is induced in response to treatment with 2‐deoxy‐ d ‐glucose (2DG) which causes energy depletion by blocking glycolysis (Jamsheer K and Laxmi, ). To analyse whether FLZ10 is also regulated by the reduction in cellular energy, its expression was checked in seedlings treated with increasing concentrations of 2DG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SnRK1 signalling cascade involves interaction of FLZ gene family members with the kinase subunits. Expression of FLZ genes is both positively and negatively regulated by energy deficit as well as energy-rich conditions (Jamsheer and Laxmi, 2015). Starvation or low energy induces expression of FLZ6, SnRK1 also induces FLZ6 during energy starvation.…”
Section: Discussionmentioning
confidence: 99%